2020
DOI: 10.3390/universe6060081
|View full text |Cite
|
Sign up to set email alerts
|

Was GW170817 a Canonical Neutron Star Merger? Bayesian Analysis with a Third Family of Compact Stars

Abstract: We investigate the possibility that GW170817 was not the merger of two conventional neutron stars (NS), but involved at least one if not two hybrid stars with a quark matter core that might even belong to a third family of compact stars. To this end, we develop a Bayesian analysis method for selecting the most probable equation of state (EoS) under a set of constraints from compact star physics, which now also include the tidal deformability from GW170817 and the first result for the mass and radius de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
82
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 96 publications
7
82
1
Order By: Relevance
“…In almost all combinations of hadronic and quark EOSs along with different values of surface tensions, the quark phase persists in the most massive compact stars, where the fraction ðM QM þ M MP Þ=M ranges from 0 to almost 1. This is in coincidence with the recent studies [127][128][129], which suggest the presence of quark-matter cores inside massive compact stars.…”
Section: Resultssupporting
confidence: 91%
“…In almost all combinations of hadronic and quark EOSs along with different values of surface tensions, the quark phase persists in the most massive compact stars, where the fraction ðM QM þ M MP Þ=M ranges from 0 to almost 1. This is in coincidence with the recent studies [127][128][129], which suggest the presence of quark-matter cores inside massive compact stars.…”
Section: Resultssupporting
confidence: 91%
“…. Here we introduced approximations of those estimates by considering a bivariate normal distribution PDF exactly as in [41]. Assuming, those two estimates are equiprobable, since they are mutually exclusive, a likelihood for M -R constraint has been introduced as follows…”
Section: Likelihood Of a Model For Mass And Radius (M -R Constraint)mentioning
confidence: 99%
“…A very important aspect shared in these Bayesian studies is the implementation of an unrestricted lower bound for the maximum neutron star mass, a quantity that keeps changing due to the observational updates, therefore influencing the posterior probabilities results [29]. The accompanying analysis [41] to our study here a) focuses on EoS models that show a third branch in the M -R diagram [42][43][44] and, b) uses the same observational constraints and Bayesian methodology used here. In addition, a more detailed overview of the state-of-the-art neutron star Bayesian studies can be found there.…”
Section: Introductionmentioning
confidence: 99%
“…But due to the presently large uncertainties in the simultaneous measurement of masses and radii, e.g., by the NICER experiment [27,28] one cannot yet select a most favorable one among them (cf. [29]). A recent study [30] has found, that EoS from the class of CSS models share the property that all M-R curves, regardless of the hybrid star onset density, must cross a small region in the M-R diagram, the SP.…”
Section: Introductionmentioning
confidence: 99%